Bean germplasm activities. Variability from interspecific hybridization - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Progress made in the genetic improvement of Phaseolus vulgaris through interspecific hybridization in 1986 included: (1) the implementation of an international yield trial for P. coccineus to assess the value of this crop, and make new germplasm available for direct use; (2) the identification of new sources of resistance to Ascochyta leaf spot in Colombia, to bean fly for which a research collaboration has been set up in Taiwan and East Africa, and to BCMV; and (3) the development of new interspecific lines to be incorporated in a next bean evaluation nursery trial. The results of these trials are presented. Interspecific hybrid lines will be sent to Guatemala, to be evaluated for resistance to Apion godmani. (CIAT)